ACCOUNTING PARADIGM WITH THE PRESENCE OF ARTIFICIAL INTELLIGENCE - Muhammad Tegar Hidayatullah; Wiwit Hariyanto (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to explore how the emergence of Artificial Intelligence (AI) has transformed the paradigm of accounting practitioners, both in professional practice and accounting education. Method: The research adopts a qualitative approach with primary data sources, using data triangulation techniques to ensure the validity and reliability of findings. The study focuses on understanding the extent to which AI influences accounting professionals’ perspectives and work processes. Results: The findings indicate that the integration of AI has opened new opportunities for accounting practitioners to enhance their knowledge and adapt to technological innovations. AI contributes to the development of efficient financial databases, improved auditing processes, and more accurate financial reporting. Novelty: This study highlights the paradigm shift among accounting practitioners toward embracing AI-driven systems, emphasizing the evolving role of accountants from traditional record-keeping to strategic data analysis and decision support in the digital era.